What regions benefit from the post-2009-crisis EU Cohesion Policy? Evidence from a Territorial Cohesion Development Index - Rauhut, Daniel (2021)
When the European Cohesion Policy (ECP) was initiated in 1989, it was designed to promote and stimulate cohesion, especially the economic and social dimensions of development (CEC, 2014). The need to encompass the ‘territorial’ dimension within the ECP emerged after the creation of the European Spatial Development Perspective (Faludi, 2006). The formal recognition of a territorial policy aspect came when ‘territorial cohesion’ was added to the policy objectives of economic and social cohesion in the Lisbon Treaty of 2009 (Faludi, 2016a; Mendez, 2011). The effects of the ECP are debated. Several studies have pointed at the positive effects of the ECP. This is definitely the case in 2000–2006 for rural regions near urban agglomerations (Gagliardi and Perocco, 2017). Although modest, the effects of the Structural Funds are long-lasting (Bradley, 2006), and the dominant view is that the ECP has had positive effects on development and economic growth (Bachtler et al., 2009; Becker et al., 2012; Cappelen et al., 2003; Molle, 2007; Pellegrini et al., 2012; Ward and Wolleb, 2010). The Objective 1 payments appear to have had a positive impact on regional economic growth; however, the total amount of Objectives 1, 2 and 3 does not (Mohl and Hagen, 2010) [...]